Elucidating the Role of Chmp1 Overexpression in the Transport of Polyamines in Drosophila melanogaster. - Stump, C.L.; Casero, R.A.; Phanstiel, O.; DiAngelo, J.R.; Nowotarski, S.L. (Medical sciences, 2022)
Polyamines are small organic cations that are essential for many biological processes such as cell proliferation and cell cycle progression. While the metabolism of polyamines has been well studied, the mechanisms by which polyamines are transported into and out of cells are poorly understood. Here, we describe a novel role of Chmp1, a vesicular trafficking protein, in the transport of polyamines using a well-defined leg imaginal disc assay in Drosophila melanogaster larvae. We show that Chmp1 overexpression had no effect on leg development in Drosophila, but does attenuate the negative impact on leg development of Ant44, a cytotoxic drug known to enter cells through the polyamine transport system (PTS), suggesting that the overexpression of Chmp1 downregulated the PTS. Moreover, we showed that the addition of spermine did not rescue the leg development in Chmp1-overexpressing leg discs treated with difluoromethylornithine (DFMO), an inhibitor of polyamine metabolism, while putrescine and spermidine did, suggesting that there may be unique mechanisms of import for individual polyamines. Thus, our data provide novel insight into the underlying mechanisms that are involved in polyamine transport and highlight the utility of the Drosophila imaginal disc assay as a fast and easy way to study potential players involved in the PTS.